Re-translations to Paratexts to Children’s Literature: The Diversity of Literary Translation - Kaloh Vid, Natalia (University of Maribor Press, 2020)
This monography consists of three sections: the testing of a re-translation hypothesis accompanied by a textual analysis of translations of Mikhail Bulgakov’s works from Russian into English, the role of metatexts, i.e. prefaces and notes, and their function and role in establishing the target readers’ interpretative coordinates and, finally, translations of children’s literature, C. Collodi’s Pinnochio and L. Carroll’s novel Alice’s Adventures in Wonderland, with an emphasis on the role of ideology and the use of domesticating strategies. I hoped to attract the reader’s attention by focusing on various aspects of literary translation and each section can be read and studied separately.